Loading of Gentamicin Sulfate into Poly (Lactic-Co-Glycolic Acid) Biodegradable Microspheres - Nojehdehian, Hanieh; Ekrami, Malihe; Jaberi Ansari, Zahra (Journal of Dental School, 2019)
Objective: In dental treatments, use of carriers for targeted antibiotic delivery would be optimal to efficiently decrease microbial count. In this study, gentamicin was loaded into polylactic co-glycolic acid (PLGA) microspheres and its release pattern was evaluated for 20 days. Methods: In this experimental study, PLGA microspheres loaded with gentamycin were produced by the W/O/W method. The correct morphology of loaded microspheres was ensured using scanning electron microscopy (SEM). The rate of drug release from polymeric microspheres into the phosphate buffered saline (PBS) solution was measured during a 20-day period using spectroscopy. Data were analyzed using one-way ANOVA. Results: SEM micrographs showed that the produced microspheres had smooth and nonporous surfaces and 30-micron diameter. Assessment of the pattern of drug release from the PLGA microspheres loaded with gentamycin revealed a burst release on day six followed by a stable pattern of release until day 20. Conclusion: Considering the biocompatibility of PLGA and optimal pattern of drug release, PLGA microspheres loaded with gentamicin can be successfully used for infection control and reduction of microbial count in dental treatments.